DYING IN HOSPITAL-IS THERE AN UNMET PALLIATIVE CARE NEED FOR PATIENTS WHO DIE WITHIN 48 HOURS OF ADMISSION?. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - Bruckner-Holt, Caroline; Baker, Alice; Aladin, Hafiz; Boulstridge, Lisa
Abstract : Background: The majority of people in the UK die in hospital and many more die in hospital than are seen by the inpatient specialist palliative care team (SPCT). Aims: To assess the population of patients who die in hospital and to establish if there are specialist palliative care needs in patients not referred to SPCT. Methods: We conducted a retrospective case note evaluation and collection of death certificate data of all 109 patients that died at Good Hope Hospital Birmingham in September 2012. We assigned Gold Standards Framework (GSF) prognostic indicator guidance to assess possible palliative care need. We assessed the time of admission to death. Results: 38/109 patients died within 48 hours of their admission and causes of death were from a range of conditions. Patients died in the emergency department or assessment units and had no SPCT involvement – 8 of these patients were known to a community SPCT, but only 1 patient was seen prior to death by the hospital SPCT. 14/38 scored 0 on GSF prognostic indicator guidance criteria (no indication of palliative care need), 15/38 scored 1, 6/38 scored 2, and 3/38 scored 3, suggesting they would benefit from a palliative care approach. Conclusion: Assessment of palliative care need using the GSF guidance can identify many patients who might benefit from SPCT involvement as they die in hospital. Many patients die within 48 hours of arriving in hospital and emergency, acute medical/surgical physicians do not identify these patients as requiring SPCT involvement. Greater education in assessment of palliative care need for these clinicians may increase referral to SPCT and improve end of life care for this patient population. SPCT will need to alter working practices, including out of hours working, if we are to have a role in the care of this group of patients as they die.